Optimization Methods for Radon Progeny Measurement Based on the Three-Stage Method - Xiangming Cai; Xuwei Zeng; Fengdi Qin; Jian Shan (Toxics)
In different measurement tasks, the duration allocated for radon progeny concentration measurement varies, and the requirements for measurement precision also differ. To accommodate the needs of various radon progeny concentration measurement tasks, this study takes the error in radon progeny concentration measurement as the optimization goal and the time points of the three-stage method as the optimization target, establishing an optimized three-stage method for radon progeny concentration measurement. The optimization algorithm allocates the three time periods under any total measurement time requirement, ensuring the highest measurement precision. The optimization algorithm can also optimize the measurement errors for 218Po, 214Pb, and 214Bi according to task requirements. By comparing with existing three-stage methods, when the total measurement time is 30 min, the optimization results are similar to Thomas’s three-stage method; when the total measurement time is 15 min, the measurement results are consistent with the rapid three-stage method. Therefore, the optimized results of the three-stage method are reasonable and reliable, providing technical support for different radon progeny measurement tasks.